Fitting-Attitude Analyses and the Relation Between Final and Intrinsic Value - C. Dussault, Antoine (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2014)
This paper examines the debate as to whether something can have final value in virtue of its relational (i.e., non-intrinsic) properties, or, more briefly put, whether final value must be intrinsic. The paper adopts the perspective of the fitting-attitude analysis (FA analysis) of value, and argues that from this perspective, there is no ground for the requirement that things may have final value only in virtue of their intrinsic properties, but that there might be some grounds for the alternate requirement that final value be grounded only in the essential properties of their bearers. First, the paper introduces the key elements of the FA analysis, and sets aside an obvious but unimportant way in which this analysis makes all final values relational. Second, it discusses some classical counterexamples to the view that final value must be intrinsic. Third, it discusses the relation between final, contributive, and signatory value. Fourth, it examines Zimmerman’s defense of the requirement that final value must be intrinsic on the grounds that final value cannot be derivative. And finally, it explores the alternative requirement that something may have final value in virtue of its essential properties.